Relationship Between Debt and Depression, Anxiety, Stress, or Suicide Ideation in Asia: A Systematic Review - Amit, Noh; Ismail, Rozmi; Zumrah, Abdul Rahim; Mohd Nizah, Mohd Azmir; Tengku Muda, Tengku Elmi Azlina; Tat Meng, Edbert Chia; Ibrahim, Norhayati; Che Din, Normah (Frontiers in Psychology, 2020)
Background: This article aims to review research manuscript in the past five years that focus on the effects of debt on depression, anxiety, stress or suicide ideation in Asian countries. Methods: A search for literature based on the PRISMA guidelines was conducted on Medline, PubMed, Web of Science, Scopus and ScienceDirect. Resulting in nine manuscripts meeting inclusion criteria. The studies were conducted in: Thailand, Korea, Singapore, Pakistan, India, Cambodia, and China. Results: The findings of the studies show that there is evidence to support that being in debt is related with Asian participants experiencing depression, anxiety, stress or suicide ideation. However, the studies are limited to quantitative studies only. The definition of debt is also unclear in most manuscripts. Few manuscripts also examined how other factors influence the relationship between debt and mental illness. Conclusion: There are limited studies on the psychological effects of debt on the Asian population. The future studies should give more attentionfocus on the relationship between debt and psychological wellbeing among this population.